Physical inactivity among health staff: what influences the behaviour? - Zakariah, Nurhaliza; Zainuddin, Huda; Ragunath, Priya; Mustapha, Feisul Idzwan (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2018)
Introduction: Physical inactivity has been recognised as the fourth leading risk factor for mortality worldwide. Individuals who are physically inactive have an increased risk of 20% to 30% of dying prematurely. Individuals who fulfil the minimum recommendations of physical activity can reduce the development of Non-Communicable Diseases. In 2015, 33.5% of Malaysian adults were reported to be physically inactive. Various factors were found to be associated with physical activity participation and these factors need to be explored. Methods: A cross-sectional study using proportionate simple random sampling was conducted. A total of 310 health staff were sampled according to the proportion from five divisions and data were collected using a self-administered questionnaire. IBM SPSS version 22.0 were used to analyse the data. Predictors for physical activity were also determined. Results: The response rate was 97.7% (303 out of 310). The prevalence of physical inactivity among respondents was 37.6%. The predictors for physical inactivity were smoker/ex-smoker (aOR=2.308, p=0.027), certificate/diploma education (aOR=2.135, p=0.008), personal barrier (aOR=1.055, p=0.017) and social environment barrier (aOR=1.106, p =0.025). Conclusion: People that have a higher possibility of being physically inactive were those with certificate or diploma education and smokers or ex-smokers. Those with personal barriers and social environment barriers likewise have higher probability of being physically inactive. Thus, appropriate health interventions should be developed by taking these factors into consideration to promote physical activity among the health staff.